An integrated RGO-pamam thin film with SPR technique for dengue virus detection - Sheh Omar, Nur Alia (2020)
The growing demand for early detection of dengue virus (DENV) has contributed to integrated thin films with surface plasmon resonance (SPR) technique, i.e. Au/Fe-NCCCTAB/ IgM, Au/CdSQDs-RGO/IgM, Au/CdSQDs-PAMAM/IgM, and Au/DSU/RGOPAMAM/ IgM. Their sensing performances such as sensitivity, binding affinity, fullwidth- half-maximum (FWHM), detection accuracy (DA), and figure-of-merit (FOM) were analysed. The first developed Au/Fe-NCC-CTAB/IgM sensor film yielded the sensitivity of 27.051 °/nM, binding affinity of 0.862 TM-1, and high performances of DA and FOM on detection of 0.001 nM of DENV E-proteins. For Au/CdSQDs-RGO/IgM sensor film, the detection performance showed the sensitivity and binding affinity values of 5.496 °/nM and 0.775 TM-1, respectively. The results also showed that the sensor film had the highest DA and FOM values when detecting 0.001 nM of DENV E-proteins. The third developed Au/CdSQDs-PAMAM/IgM sensor film showed the sensitivity of 7.577 °/nM, binding affinity of 2.696 TM-1, and high performances of DA and FOM on detection of 0.001 nM of DENV E-proteins. The final development of SPR sensor integrated Au/DSU/RGOPAMAM/ IgM sensor film resulted in the sensitivity of 10.939 °/nM, binding affinity of 9.783 TM-1, and high performances of DA and FOM on detection of 0.0001 nM of DENV E-proteins. Structural investigations using Raman spectroscopy, Ultraviolet-visible near infrared (UV-Vis-NIR) spectroscopy, and Atomic force microscopy (AFM) have confirmed the presence of the conjugate DENV E-proteins-antibodies-nanocomposite layer. Most importantly, by comparing the performances of the sensor films described above, the results found that the Au/DSU/RGO-PAMAM/IgM is a very effective sensor film because it has the lowest quantitation limit and strongest binding affinity. Despite its low sensitivity, the sensitivity of detection was further enhanced by optimizing the fabrication of Au/DSU/RGO-PAMAM/IgM sensor film. The excellent sensitivity and binding affinity constant obtained were 333.896 °/nM and 9.345 TM-1, respectively. High performance of DA, FOM, selectivity, stability, reproducibility, and spike-recovery were achieved at DENV E-proteins concentration of 0.00008 nM (0.8 fM), indicating the best concentration limit obtained so far. In addition, this sensor film demonstrated a real-time DENV Eproteins detection within 8 minutes. Studies from structural measurements have successfully showed the presence of functional groups, absorption band shifts, and increased in surface roughness values from 1.56 nm to 3.19 nm due to the binding event of sensing layer to DENV E-proteins.